In-plane charged antiphase boundary and 180° domain wall in a ferroelectric film - Cai, Xiangbin (2024)
The deterministic creation and modification of domain walls in ferroelectric films have attracted broad interest due to their unprecedented potential as the active element in non-volatile memory, logic computation and energy-harvesting technologies. However, the correlation between charged and antiphase states, and their hybridization into a single domain wall still remain elusive. Here we demonstrate the facile fabrication of antiphase boundaries in BiFeO3 thin films using a He-ion implantation process. Cross-sectional electron microscopy, spectroscopy and piezoresponse force measurement reveal the creation of a continuous in-plane charged antiphase boundaries around the implanted depth and a variety of atomic bonding configurations at the antiphase interface, showing the atomically sharp 180° polarization reversal across the boundary. Therefore, this work not only inspires a domain-wall fabrication strategy using He-ion implantation, which is compatible with the wafer-scale patterning, but also provides atomic-scale structural insights for its future utilization in domain-wall nanoelectronics.